2014
DOI: 10.1039/c4cp02552k
|View full text |Cite
|
Sign up to set email alerts
|

Line defects and induced doping effects in graphene, hexagonal boron nitride and hybrid BNC

Abstract: Effects on the atomic structure and electronic properties of two-dimensional graphene (G) and h-BN sheets related to the coexistence of dopants and defects are investigated by using density functional theory based methods. Two types of extended line defects are considered for pristine G and h-BN sheets. In these sheets, the presence of individual doping increases the charge transport character. The coexistence of dopants and defects tunes the band gap towards lower values and causes the direct-indirect band ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 80 publications
2
31
0
Order By: Relevance
“…On the other hand, the capability of controlling which device region will be associated with current flow (essentially creating a one-dimensional wire), combined with the enhanced reactivity of sites in extended topological defects in graphene [25,26], could make o-p and h-p systems promising candidates for bio-and gas sensor applications. Although both systems studied here are stable from the theoretical point of view [31,49,50], the o-p line defect has been synthesized in a highly controlled manner [3,6] and has a lower formation energy.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the capability of controlling which device region will be associated with current flow (essentially creating a one-dimensional wire), combined with the enhanced reactivity of sites in extended topological defects in graphene [25,26], could make o-p and h-p systems promising candidates for bio-and gas sensor applications. Although both systems studied here are stable from the theoretical point of view [31,49,50], the o-p line defect has been synthesized in a highly controlled manner [3,6] and has a lower formation energy.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these line defects are tilt boundaries separating two domains of different lattice orientations with the tilt axis normal to the plane. Such defects can be thought of as a line of reconstructed point defects with or without dangling bonds [18][19][20] , as shown in Fig. 3.…”
Section: One Dimensional Defectsmentioning
confidence: 99%
“…[26][27][28][29] . However, relatively few studies have addressed doping in extended line defects 21,30 . First-principle calculations of the substitution formation energies by Brito et al 30 have shown that nitrogen doping is thermodynamically more favored in the vicinity of a line defect compared to the graphene region.…”
mentioning
confidence: 99%